Research on World Food Production Efficiency and Environmental Sustainability Based on Entropy-DEA Model - Min Zhang; Wen-Kai Cui; Yu-Jing Zhang; Yun-Hua Xu (Complexity)
At present, the contradiction between the high efficiency of the world’s food production and environmental pollution is becoming increasingly prominent. In order to study the related issues of the world’s food production efficiency and sustainability, this paper uses the method of entropy weight to extract 5 indicators as the environmental pollution assessment model from the environmental pollution of agricultural production, scores 10 major agricultural production countries in the world, and obtains the environmental pollution index. Subsequently, the DEA model was established for these countries, the environmental pollution index was included into the production efficiency system as an unexpected output, the Malmquist index was established to describe the changes in agricultural production efficiency from 2010 to 2018, and the cluster analysis was carried out for it. Subsequently, the OSL and Tobit models were used for regression of the influencing factors. In addition, the comprehensive evaluation model of efficiency and sustainability was established by controlling the amount of fertilizer used, which was applied in different countries.